ANALYSIS OF CRIMINAL LIABILITY FOR THE CRIMINAL ACTS OF USING FORGED LETTERS AND THE CRIMINAL ACTS OF MONEY LAUNDERING (Study of Judge's Decision Number 432/Pid.B/2021/PN. Jkt. Sel.) - Muhammad Luthfi Seviansyah; Nurmalawati -; Marlina - (NOMOI Law Review, 2026)
A deed of sale and purchase of land is a legal document that evidences the transfer of ownership rights from the previous owner to the new owner, executed by a Land Deed Official (PPAT) or a notary. Such deeds are not immune from forgery, often committed for personal gain and to the detriment of others. In committing criminal offenses, perpetrators frequently act with the intention of obtaining financial benefit. These illicit gains may be subsequently disguised through acts of money laundering, as occurred in the case reviewed in Court Decision Number 432/Pid.B/2021/PN Jkt. Cell. This thesis addresses the legal regulation of the offense of document forgery, the legal regulation of money laundering offences, and the criminal liability of offenders who use forged deeds of sale and purchase of land and engage in money laundering. The method employed in this research is normative legal research, applying a qualitative approach, with data collected through a literature study. Based on the findings, the offense of document forgery and the use of forged documents is regulated under Articles 263 and 264 of the Indonesian Penal Code (Criminal Code, KUHP), while under Law No. 1 of 2023, these offenses are governed by Articles 391 and 392. The offense of money laundering is regulated under Article 3 of Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering, and under Law No. 1 of 2023, it is governed by Articles 607 and 608. In the application of criminal sanctions in Decision Number 432/Pid.B/2021/PN Jkt. Sel., the judge referred to Article 263 paragraph (2) concerning the use of forged documents in conjunction with Article 55 paragraph (1) point 1 of the Penal Code, as well as Article 3 of Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering in conjunction with Article 55 paragraph (1) point 1 of the Penal Code